(untitled) (Acta Entomologica Serbica, 2022)
Disepyris Kieffer, a small genus of Bethylidae (Hymenoptera), is recorded for the first time from Iran, represented by D. niveus Lim & Azevedo. Members of this genus can be easily recognized by the protarsi of females with delicate long spines and forewing with short 2r-rs&Rs vein. The diagnostic characters of species are briefly presented according to the newly collected specimens with reference to the respective illustrations.